Analysis of current status and influencing factors of participation in medication safety behaviors among older adult patients with chronic co-morbidities: based on the COM-B model - Li, Yuxin; He, Lin; Zhao, Tianxia; Dai, Ping; Wen, Yanhong; Fan, Yuting; Lin, Qin; Wu, Jijun (Frontiers in Public Health, 2025)
BackgroundWith the acceleration of global aging, the prevention and control of chronic disease comorbidity have become increasingly challenging, emerging as a significant global public health issue. Patients with multiple coexisting conditions often face complex treatment regimens and multiple medications, posing significant challenges to their participation in medication safety behaviors. Individual health behaviors are influenced by knowledge, beliefs, and social environment, among other factors. Therefore, this study employs the COM-B model to analyse the factors influencing participation in medication safety behaviors among older adult patients with chronic coexisting conditions, aiming to provide insight into participation in medication safety behaviors.MethodsThis cross-sectional study employed convenience sampling to survey 335 older adult patients with chronic disease comorbidity at a Grade A tertiary hospital in Sichuan Province, China, from July to December 2024. The survey employed a general information questionnaire, the participation in medication safety behaviors scale, the health literacy scale, the medication belief scale, the family APGAR questionnaire, and the social network scale. Descriptive analysis, univariate analysis, correlation analysis, and multiple linear regression analysis were conducted using SPSS 26.0 software.ResultsThe mean participation in medication safety behaviors score among 335 older adult patients with chronic comorbidities was 101.36 ± 16.68. Correlation analysis revealed that the total score and individual dimension scores of participation in medication safety behaviors among older adult patients with chronic comorbidities were positively correlated with the total scores of health literacy, medication belief, family function, and social network (r = 0.347–0.703, p < 0.01). Multivariate linear regression analysis revealed that education level, drug concerns, disease knowledge level, health literacy, medication belief, family function, and social network were significant predictors in the regression equation (p < 0.05), accounting for 75.5% of the total variance.ConclusionChinese older adult patients with chronic disease comorbidity demonstrate moderate participation in medication safety behaviors. Education level, drug concerns, disease knowledge level, health literacy, medication belief, family function, and social network are key determinants influencing medication safety behaviors among this population. The COM-B model provides a framework for explaining low participation in medication safety behaviors among older adult patients with chronic disease comorbidities and guides the development of targeted health intervention strategies.